Associations between maternal concern about child's weight and related behaviours and maternal weight-related parenting practices: a cross-sectional study - Jess Haines; Katherine L. Downing; Lisa Tang; Karen J. Campbell; Kylie D. Hesketh (BMC, 2018)
Abstract Background Parents influence their children's weight-related behaviours through their parenting practices, which are often a focal point of obesity prevention interventions. This study examined associations of maternal concern about their child's weight, dietary intake, physical activity, and media use with maternal food, physical activity, and media parenting practices. Methods Mothers (n = 310) reported their level of concern regarding their child's weight and related behaviours and their weight-related parenting practices when their child was 5 years of age as part of the Melbourne Infant Feeding Activity and Nutrition Trial (InFANT) Program. We used linear regression analyses with estimation by generalized estimating equations to examine associations of maternal concern and maternal parenting practices. Results Slightly more than 60% of mothers reported at least one concern related to their children's weight or related behaviours. Excessive media use was the most commonly endorsed concern among mothers (45.2%). Compared to mothers who were unconcerned about their child's weight, mothers who were concerned about their child weighing too much reported higher levels of controlling feeding practices, i.e., restrictive feeding, lower levels of co-participation of physical activity, and higher levels of using media to control child behaviour. Mothers who were concerned their child weighed too little reported higher levels of controlling feeding practices, i.e., restrictive feeding, pressure to eat. Similarly, mothers who were concerned about their child's eating (eating too much or too little) reported higher levels of controlling feeding practices. Mothers who were concerned about their child using too much media reported higher levels of using media to regulate their child's behaviour and providing opportunities for their child to use media. Conclusion Mothers who were concerned about their child's weight, dietary intake, physical activity and media use reported higher levels of controlling parenting practices, i.e., pressure to eat, and lower levels of health promoting parenting practices, i.e., co-participation in physical activity. Longitudinal research is needed to elucidate temporal order and specific mechanisms of these associations.